Dompet Dhuafa Waspada Communication Strategy to Attract the Community to Achieve the Target of Zakat Collection in Medan City - Pathurohman Pathurohman; Hasrat Efendi Samosir; Azhar Azhar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The aims of this study are to find out Dompet Dhuafa Waspada Communication Strategy to Attract the Community to Achieve the Target of Zakat Collection in Medan City. This study uses qualitative reseach method. The result of this study shows that That Dompet Dhuafa Alert is a National Amil Zakat Institution. In order for the management of zakat and the function of Dompet Dhuafa Waspada to be known by the general public, it is necessary to disseminate information on the expansion of information. In socializing zakat, it is necessary to have a communication strategy so that the public can know how Dompet Dhuafa Waspada in managing zakat, in recognizing and understanding what zakat is and Dompet Dhuafa Waspada. The Head of SPV Fundraising and Marketing Communication plays a very important role in carrying out communication strategies in attracting public interest in achieving the target of collecting zakat in Medan City.The communication strategy in attracting public interest in achieving the target of zakat collection in Medan City used is by recognizing communication targets, educative communication strategies, communication strategies using media both online and offline. The communication strategy used is to know the target of communication, convey information, education and enlightenment through lectures and seminars to the public about zakat. Then communication is carried out in various ways, there are through both social media such as Instagram, Facebook, websites and also through mass media such as collaborating with the Waspada Daily newspaper, there is also the distribution of banners, x banners, and the distribution of bulletins. And the institution also communicates face-to-face with the way the Dompet Dhuafa Waspada comes to the public or donors and if it is not possible directly then greets by telephone. and the efforts made by Dompet Dhuafa Waspada are by communicating transparency to muzakki by publishing reports on financial inflows and outflows. The aim is to increase the trust of muzakki and parties related to Dompet Dhuafa Waspada, North Sumatra.